Case Based Reasoning Method untuk Sistem Pakar Diagnosa Penyakit Sapi - Muzakkir, Irvan; Botutihe, Marniyati Husain (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2020)
This study discusses about the Application of Case Based Reasoning (CBR) Method for Expert Systems in Diagnosing Cattle Disease. Beginning with data collection by consulting experts in the Department of Agriculture in Animal Health, Pohuwato Regency. The data obtained in the form of data names of disease and symptom data. The data is obtained based on the steps of the CBR method calculation in order to obtain the results of the diagnosis and the solution provided for handling the disease. Researcher have analyzed and create program listings to build a system that will be used by farmers. Based on CBR calculations Scours case which has the lowest weight is 0.09 while the highest weight is owned by the Pink Eye case 1. In this process provides a solution to the similarity of the case weight from the old case to the new higher case. In the case of Pink Eye having a higher weight and positive exposure to pink eye disease, the solution given is the provision of anti-allergic, anti-biotic and vitamin. Based on the results obtained, it can be concluded that the application of the CBR method is good for using cattle disease and is very helpful for farmers in dealing with cattle disease.